Nora Ephron a biography - Doidge, Kristin Marguerite (Chicago Review Press, 2022)
"Nora Ephron: A Biography is the first comprehensive portrait of the Manhattan-born girl who forged a path of her own, earning accolades and adoration from critics and fans alike. Author Kristin Marguerite Doidge explores the tremendous successes and disappointing failures Ephron sustained in her career as a popular essayist turned screenwriter turned film director. She redefined the modern rom-com genre with bestselling books such as Heartburn and hit movies including When Harry Met Sally, Sleepless in Seattle, and Julie & Julia. Doidge also examines the private life Ephron tried to keep in balance with her insatiable ambition. Based on rare archival research and numerous interviews with some of Ephron's closest friends, collaborators, and award-winning colleagues including actors Tom Hanks and Caroline Aaron, comedian Martin Short, composer George Fenton, and lifelong friends from Wellesley to New York to Hollywood--as well as interviews Ephron herself gave throughout her career--award-winning journalist and cultural critic Doidge has written a captivating story of the life of a creative writer whose passion for the perfect one-liner and ferocious drive to succeed revolutionized journalism, comedy, and film"--